„Burgenland” kartográfiai ábrázolása (atlaszok Burgenlandról) = Cartographic representation of “Burgenland” (atlases of Burgenland) - Suba, János (Közép-Európai Közlemények, 2018)
In the history of Austria after 1921 only two atlases were made in term of cartography, which depict the history and geography of Burgenland. The aim of the present study is to review them. The 1941 Burgenland atlas is a logically built and edited map work. The dimension, the scale and the generalization principle are all uniform. The colour and name use of the maps are consistent on the map pages. This atlas is a well developed and understandable work. It reviews the history of Burgenland with a series of maps (440 pieces). The 2011. Historischer Atlas Burgenland is a diverse historical educational work, on the contrary to its title. The emphasis is on the texts with the maps being only the supplement of theirs. Most of the pages come from other works without indicating the sources. The drawing of the maps is modest. The key is different for each map. There is no scale or even rate on them. Neither the colour use nor the dimension is uniform.